2020
DOI: 10.1080/08827508.2020.1806835
|View full text |Cite
|
Sign up to set email alerts
|

Transport Phenomena in Copper Bath Smelting and Converting Processes – A Review of Experimental and Modeling Studies

Abstract: Bath smelting and converting technologies for copper production have been improved, resulting in higher production efficiency and less polluting emissions. Reported studies on experimental and computational modeling approaches are reviewed in this paper, focusing on adjustable variables and flow details, for a thorough understanding of the complex flow phenomena of the high-temperature reactors used. Results from water models and Computational Fluid Dynamics (CFD) simulations indicate that the transport phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…A quantified low velocity region volume fraction for different melt density is displayed in Fig. 6(d), showing that in the simulated 0-30 s, the volume fractions of the low velocity regions for a density of 4000 kg/m 3 and 5000 kg/m 3 are interlaced, and the volume fraction for a density of 3000 kg/m 3 is mostly below that of the density 5000 kg/m 3 .…”
Section: The Effect Of Melt Densitymentioning
confidence: 98%
See 1 more Smart Citation
“…A quantified low velocity region volume fraction for different melt density is displayed in Fig. 6(d), showing that in the simulated 0-30 s, the volume fractions of the low velocity regions for a density of 4000 kg/m 3 and 5000 kg/m 3 are interlaced, and the volume fraction for a density of 3000 kg/m 3 is mostly below that of the density 5000 kg/m 3 .…”
Section: The Effect Of Melt Densitymentioning
confidence: 98%
“…Therefore, some adjustments do not always result in smooth operation, and once the practical requirements are not met, for instance, when the lining refractories are subjected to strong impact and erode unexpectedly, extra furnace operation costs are incurred. Scientific SKS furnace modeling research is necessary to achieve better operation [3]. To support the industrial demand for better furnace operating performance, CFD modeling studies have been widely conducted and reported [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Mixing behaviour [45][46][47][48][49][50][51], surface wave [52,53], plume eye [54], bubble behaviour [55][56][57][58], fluctuating behaviour [59] were studied by water model to simulate the molten bath in BBF. Lance arrangement [60][61][62], gas-liquid multi-phase flows [63][64][65], flow and mixing behaviour [66] and multiphase interface behaviours [67,68] in the BBF were studied by the CFD method.…”
Section: Fluid Dynamic Studiesmentioning
confidence: 99%
“…In the pyrometallurgical production of copper, one of the important points when melting sulfide copper concentrates in smelting furnaces is the reduced content of magnetite in the waste slag. For example, in a reverberatory furnace, magnetite in an amount of 2-9% can be supplied with the concentrate [[17, [18], [19], [20]].…”
Section: Introductionmentioning
confidence: 99%